Changes in the composition of the lactic acid bacteria behavior and the diversity of oenococcus oeni isolated from red wines supplemented with selected grape phenolic compounds - Collombel, Ingrid (2019)
Phenolic compounds are important components of wine and are known to have an impact on the physiology of wine microbes. The influence of specific sub-sets of phenolic compounds on the growth and metabolism of lactic acid bacteria (LAB) and on the diversity of Oenococcus oeni in inoculated and non-inoculated red wines was investigated during malolactic fermentation (MLF) and subsequent storage. Representative O. oeni strains from wines treated with flavonols and trans-resveratrol were isolated and analyzed by pulsed-field gel electrophoresis of rare restriction enzyme digests (REA-PFGE). 28 days after MLF initiation, strains from all samples had entered the death phase, except those supplemented with trans-resveratrol. In the non-inoculated samples, the onset of lactic acid production was apparently delayed by all compounds tested, except for the flavan-3-ols. Increased levels of phenolics also delayed citrate consumption in inoculated samples. PFGE analysis revealed 22 genetic profiles, and some profiles were characteristics of specific samples. The commercial starter used in the inoculated wines did not dominate during MLF. The effect of the phenolics studied was dependent on the origin and concentration of each as well, as the fermentation stage and whether the wines were inoculated. The effect of flavonols and trans-resveratrol seemed to be strain-dependent, which could have implications on the final quality of wines.